Mothers' experiences of quality of care and potential benefits of implementing the WHO safe childbirth checklist: a case study of Aceh Indonesia - Siobhan Doria; Farah Diba; Suryane S. Susanti; Sebastian Vollmer; Ida G. Monfared (BMC, 2019)
Abstract Background In an effort to mitigate missed opportunities to provide high-quality care, the World Health Organization (WHO) has developed the Safe Childbirth Checklist (SCC) to support health providers perform essential tasks. Our qualitative study is a baseline assessment of quality of care (QoC) perceived by mothers who gave birth at health facilities aiming to highlight areas where implementing the SCC can potentially improve the QoC as well as areas that are not part of the SCC yet require improvement. Methods Assessing the overall experience of care, our qualitative study focuses on 8 out of 29 items in the checklist that are related to the personal interactions between healthcare provider and mothers. Using a set of semi-structured questions, we interviewed 26 new mothers who gave institutional births in Aceh province in Indonesia. Results Our findings revealed some gaps where implementing the SCC can potentially improve safety and QoC. They include communicating danger signs at critical points during birth and after discharge, encouraging breastfeeding, and providing mothers with information on family planning. Moreover, taking a qualitative approach allowed us to identify additional aspects such as need for clarity at the point of admission, maintaining dignity, and protecting mothers' rights in the decision-making process to be also essential for better QoC. Conclusions Our study highlights the need to actively listen to and engage with the experiences of women in the adaptation and implementation of the checklist. While our findings indicate that implementing the SCC has the potential to improve the quality of maternal care and overall birth experience, a more holistic understanding of the lived experiences of women and the dynamics of their interactions with health facilities, care providers, and their birth companions can complement the implementation of the checklist.